Protective effects of Ginkgo biloba against rat liver carcinogenesis - Dias, Marcos C. [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP]; Reimberg, Maria C. H.; Barbisan, Luis Fernando [UNESP] (Elsevier B.V., 2008)
Ginkgo biloba (EGb) has been proposed as a promising candidate for cancer chemoprevention and has shown protective effects on the liver against chemically induced oxidative injury and fibrosis. The potential beneficial effects of EGb were investigated in two rat liver carcinogenesis bioassays induced by diethylnitrosamine (DEN). In a short-term study for anti-initiating screening, male Wistar rats were fed a basal diet or supplemented diet with 500 or 1000 ppm EGb and initiated 14 days later with a single dose of DEN (100 mg/kg i.p.). The respective groups were killed 24 h or 2 weeks after DEN-initiation. Liver samples were collected for the analysis of proliferating cell nuclear antigen (PCNA), transforming growth factor alpha (TGF-alpha), p53, apoptosis and induction of single hepatocytes and minifoci positive for the enzyme glutathione S-transferase P-form (GST-P). In a medium-term study for anti-promoting screening, the animals received a single dose of DEN (200 mg/kg i.p.) and, 2 weeks later, were fed a basal diet or supplemented diet with 500 or 1000 ppm EGb for 6 weeks. All animals underwent 70% partial hepatectomy (PH) at week 3 and killed at week 8. Liver samples were colleted to analyze development of preneoplastic foci of altered hepatocytes (FAH) expressing GST-P. In the short-term study, pretreatment of rats with 1000 ppm EGb significantly reduced the rates of cell proliferation, apoptosis and p53, TGF-a immunoreactivity and the number of GST-P-positive hepatocytes. In the medium-term study, EGb treatment during the post-initiation stage failed to reduce the development of DEN-induced GST-P-positive foci. Thus, EGb presented inhibitory actions during initiation but not promotion of rat liver carcinogenesis induced by DEN. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: diethylnitrosamine; putative initiated hepatocytes; GST-P-positive preneoplastic foci; liver carcinogenesis; Ginkgo biloba; chemoprevention